Coronary calcium score in 12-year breast cancer survivors after adjuvant radiotherapy with low to moderate heart exposure – Relationship to cardiac radiation dose and cardiovascular risk factors. Issue 3 (March 2015) - Tjessem, Kristin Holm; Bosse, Gerhard; Fosså, Kristian; Reinertsen, Kristin V.; Fosså, Sophie D.; Johansen, Safora; Fosså, Alexander
Abstract Background/purpose We explored the relation between coronary artery calcium (CAC) and cardiac radiation doses in breast cancer survivors (BCS) treated with radiotherapy (RT). Additionally, we examined the impact of other risk factors and biomarkers of coronary artery disease (CAD). Materials and methods 236 BCS (median age 51 years [range 30–70], median observation time 12 years [9.2–15.7]), treated with 4-field RT of 50GY, were included and examined in 2004 (T1), 2007 (T2) and 2011 (T3) with clinical examination, blood tests and questionnaires. At T3, cardiac computed tomography was performed with quantification of CAC using Agatston score (AS). For 106 patients cardiac dose volume histograms were available. Results The cohort-based median of the mean cardiac dose was 2.5 (range 0.5–7.0) Gy. There was no correlation between measures of cardiac dose and AS. AS was correlated with high cholesterol at T1/T2 (p = 0.022), high proBNP at T1/T2 (p < 0.022) and T3 (p < 0.022) and high HbA1c at T3 (p = 0.022). In addition, a high AS was significantly associated with hypertension (p = 0.022). Age (p < 0.001) and cholesterol at T1/T2 (p = 0.001) retained significant associations in multivariate analysis. Conclusions Traditional, modifiable risk factors of CAD correlate with CAC and may be important for the long term risk of CAD after RT. With low to moderate cardiac radiation exposure, a contribution of radiation dose to CAC could not be demonstrated.